TECHNOLOGY OF USING TEXTBOOKS DESCRIBING EVENTS AND EVENTS IN NATURAL GEOGRAPHY OF CENTRAL ASIA AND UZBEKISTAN (Conference Zone, 2022)
In teaching the natural geography of Central Asia and Uzbekistan in secondary schools, the use of teaching aids describing events and happenings and meaningful lessons.